Corporate Governance and Firm Performance: Evidence from Deposit Money Bank in Nigeria - Ibrahim, Abdurrashid; Aderemi Daniel, Adekanmi; Oladipo, Olaniyan Niyi; Banji Rildwan, Olaleye (EuroEconomica, 2023)
This study examined the effect of corporate governance on firm performance in Nigeria, It specifically examined the effect of board director and managerial ownership on profit after tax of listed deposit money bank in Nigeria. Secondary source of data were employed through ex post facto research design. Census sampling technique was employed for the fourteen listed Deposit Money Bank spanning for the period of 2010-2020 .84 observation were assessed using multiple regression model. A strong multiple regression model was used to analyze the nexus between board of directors and managerial ownership. The multiple regression result of the findings showed that board size has positive and significant effect on profit after tax with a coefficient of 0.319 at 0.005 level of significance, while managerial ownership has negative and significant effect on profit after tax with a coefficient of 0.102 at 0.005 level of significant (p=0.045).It was concluded that corporate governance has significant effect of firm performance of listed Deposit Money Bank in Nigeria Exchange Group. However it was recommended that agency problem between manager and owners may be mitigated by keeping managerial ownership stake in a company low. This can assist keep costs down in the event of bankruptcy and provide for better oversight and control of management. With improved corporate governance provided by a larger board, firms may find it less difficult to get access to cheaper types of external capital, hastening the desired leverage ratio.